2014
DOI: 10.1007/s00520-014-2279-z
|View full text |Cite
|
Sign up to set email alerts
|

Desire for children, difficulties achieving a pregnancy, and infertility distress 3 to 7 years after cancer diagnosis

Abstract: PurposeThe aim was to investigate desire for children, difficulties achieving a pregnancy, and infertility distress among survivors 3 to 7 years after cancer treatment in reproductive age.MethodsCancer survivors were identified in national population-based cancer registries. Eligible subjects presented with selected cancer diagnoses between 2003 and 2007 between the ages of 18 to 45. A postal questionnaire including study-specific questions, the Short-Form 36 Health Survey and the Fertility Problem Inventory, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
115
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(120 citation statements)
references
References 40 publications
4
115
1
Order By: Relevance
“…One of the reasons for conducting the present study was the previous results from our research group [2,3,25], showing that female patients receive less information about the treatment-related impact on fertility and FP than males. We therefore inquired separately about the fertility discussions with female and male patients, and conducted all analyses separately for the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the reasons for conducting the present study was the previous results from our research group [2,3,25], showing that female patients receive less information about the treatment-related impact on fertility and FP than males. We therefore inquired separately about the fertility discussions with female and male patients, and conducted all analyses separately for the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is rational for most cancer patients to prioritize survival over fertility, having children remains an important life goal after being treated for cancer [2,3]. Moreover, treatment-induced infertility is associated with emotional distress [2] and depression [4]. The American Society of Clinical Oncology recommends the early provision of information on the risks to fertility associated with cancer treatment and on fertility preservation (FP) to all patients of reproductive age [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Indeed, the CCSS reported that 6.3% of childhood survivors experience acute ovarian failure immediately after treatment, and 8% experience premature ovarian failure at some point after the end of treatment. 5,6 Preservation and restoration of fertility are key aspects for enhancing quality of life in this population, and studies have found that 60% of survivors desire to rear biological children and >65% of childhood or young adult cancer survivors have used or want information about infertility and options for having children. [7][8][9][10][11] Thus, major emphasis has been placed on research in the area of childhood cancer survivors, directed not only at providing a cure for their cancer, but at a treatment approach that will allow for the best possible quality of life into adulthood.…”
mentioning
confidence: 99%
“…One-third of the young adult cancer survivors surveyed in this study had already experienced problems conceiving, and fertility problems were associated with moderate distress. 19 Cancer patients' attitudes toward infertility and FP Infertility may be unanticipated and may come as a shock to cancer survivors, particularly those who have been inadequately counseled about fertility. 20,21 Beyond the loss of ability to have children, infertility may be perceived as a loss of masculinity or femininity.…”
mentioning
confidence: 99%